Processo de separação por membranas na purificação de ficocianina de Spirulina sp. - Sbeghen, Alessandro Lima (2016)
Phycocyanin is a photosynthetic pigment of the phycobiliprotein family, its chromophore group conferring in addition to the blue staining of cyanobacteria,anticarcinogenic, anti-inflammatory and antioxidant properties, among other pharmacological properties. Its properties, which allowed dried algae to last for long periods, stimulated studies for the substitution of synthetic antioxidants due to their deleterious effects. In addition tothe use of phycocyanin as a dye in the cosmetics and food industries, its bioactive properties generate a product of high added value and of great interest in these industries. Purification of phycocyanin obtained from the crude extract of microalgae such as Spirulina sp and carried out by membrane separation processes may make this operation simpler and easier to stagger. For the purification process, the extraction methods, different types of membranes, their efficiency and fouling to obtain food-grade phycocyanin and antioxidant activity were evaluated. The microalga was subjected to extraction by freezing and thawing obtained a crude cellular extract containing 1.38 mg.mL-1and with a degree of purity of 0,353. This crude extract was subjected to the separation process by flat membranes of 20 μm, 0.4 μm and 60 kDa for purification, however the fouling produced in this process was very high, preventing the obtaining of a pur ified extract. Looking for another methodology of extraction was tested freeze-thaw extraction, ultrasonic bath and phosphate buffer solutions, being this last a better extraction result. The crude extract obtained by phosphate buffer solution obtained a 58.54 mg.g-1 extraction of phycocyanin per g of cell and a grade of purity of 0.52. This crude extract was subjected to an ultrafiltration process by a tubular membrane in pilot equipment, followed by three diafil trations. The purification process was efficient, reaching values of 0.83 for purity grade with purification factor of 1.54 and keeping antioxidant properties. The membrane separation process showed to have ease scaleup and capacity for phycocyanin purification on a large scale.